2004
DOI: 10.1016/j.jde.2004.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Moser's theorem for lower dimensional tori

Abstract: Moser’s C-version of Kolmogorov’s theorem on the persistence of maximal quasi-periodic\ud solutions for nearly-integrable Hamiltonian system is extended to the persistence of non-maximal\ud quasi-periodic solutions corresponding to lower-dimensional elliptic tori of any dimension n\ud between one and the number of degrees of freedom. The theorem is proved for Hamiltonian\ud functions of class C for any >6n + 5 and the quasi-periodic solutions are proved to be of\ud class Cp for any p with 2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…The proof of existence of elliptic (stable) lower-dimensional tori in the general case was given by Eliasson [6]. For an overview of the results on lower-dimensional tori, the reader is referred to [4,[6][7][8][9][10]22,24,25,27,29,32]. Lowerdimensional tori also appear in and are particularly relevant for PDEs (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The proof of existence of elliptic (stable) lower-dimensional tori in the general case was given by Eliasson [6]. For an overview of the results on lower-dimensional tori, the reader is referred to [4,[6][7][8][9][10]22,24,25,27,29,32]. Lowerdimensional tori also appear in and are particularly relevant for PDEs (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Such approach applies to some PDEs with periodic boundary condition (see [2]). Especially, when the small perturbations f i (i = 1, 2, 3, 4) are functions of class C d (d > 6n + 5) and normal frequencies Ω i are simple, Chierchia and Qian [3] showed the persistence and regularity of the lower n-dimensional elliptic tori.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of finitely differentiable perturbations, the study on the persistence of quasi-periodic invariant tori has originated from the work of Moser [24] on area-preserving mappings of an annulus, which was extended to dissipative vector fields in [6] based on smoothing operator technique. Another important method, which can relax the requirement for regularity of perturbations, is to approximate a differentiable function by real analytic ones [25,30,40,27,35,13,1,38]. Rüssmann [30] proved an optimal estimate result on approximating a differentiable function by analytic ones.…”
mentioning
confidence: 99%
“…Following this approach Zehnder [40] established a generalized implicit function theorem and applied it to the existence of parameterized invariant tori of nearly integrable Hamiltonian systems in finitely differentiable case, Pöschel [27] showed that on a Cantor set, invariant tori of the perturbed Hamiltonian system form a differentiable family in the sense of Whitney. The results and ideas of Moser and Pöschel are extended to the case of symplectic mappings by Shang [35] and to the case of lower dimensional elliptic tori by Chierchia and Qian [13], respectively. Wagener [38] extended the modifying terms theorem of Moser [26] (i.e., introducing additional parameters) to finitely differentiable and Gevrey regular vector fields.…”
mentioning
confidence: 99%
See 1 more Smart Citation